Association of common variants in JAK2 gene with reduced risk of Metabolic Syndrome and related disorders - Penas Steinhardt, Alberto (2011)
Background: Disturbances in leptin and insulin signaling pathways are related to obesity and metabolic syndrome (MS) with increased risk of diabetes and cardiovascular disease. Janus kinase 2 (JAK2) is a tyrosine kinase involved in the activation of mechanisms that mediate leptin and insulin actions. We conducted a population cross-sectional study to explore the association between two common variants in JAK2 gene and MS related traits in 724 Argentinean healthy male subjects. Methods A total of 724 unrelated men aged 37.11 ± 10.91 yr were included in a cross-sectional study. Physical examination, anthropometric measurements and biochemical analysis were determined by a standardized protocol. rs7849191 and rs3780378 were genotyped. Analyses were done separately for each SNP and followed up by haplotype analysis. Results rs7849191 and rs3780378 were both associated with reduced risk of MS [p = 0.005; OR (95%CI) = 0.52 (0.33-0.80) and p = 0.006; OR (95% CI) = 0.59 (0.40-0.86) respectively, assuming a dominant model]. rs3780378 T allele was associated with triglyceridemia values under 150 mg/dl [p = 0.007; OR (95%CI) = 0.610 (0.429-0.868)] and TT carriers showed lower triglycerides (p = 0.017), triglycerides/HDL-C ratio (p = 0.022) and lipid accumulation product (p = 0.007) compared to allele C carriers. The two-SNPs-haplotype analysis was consistent with single locus analysis. Conclusions It was found for the first time, significant associations of JAK2 common variants and related haplotypes with reduced risk of MS. These findings could be explained by the role of JAK2 in insulin and/or leptin signaling.